2003
DOI: 10.1109/tie.2003.817609
|View full text |Cite
|
Sign up to set email alerts
|

A review of single-phase improved power quality ac~dc converters

Abstract: Abstract-Solid-state switch-mode rectification converters have reached a matured level for improving power quality in terms of power-factor correction (PFC), reduced total harmonic distortion at input ac mains and precisely regulated dc output in buck, boost, buck-boost and multilevel modes with unidirectional and bidirectional power flow. This paper deals with a comprehensive review of improved power quality converters (IPQCs) configurations, control approaches, design features, selection of components, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
389
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,158 publications
(436 citation statements)
references
References 355 publications
0
389
0
7
Order By: Relevance
“…The basic circuit of PFC [10] is quite simple but it does not provide the acceptable values of total harmonic distortion (THD) of the input current. To improve the values of THD the multiphase topology of PFC is applied.…”
Section: The Charger Designmentioning
confidence: 99%
“…The basic circuit of PFC [10] is quite simple but it does not provide the acceptable values of total harmonic distortion (THD) of the input current. To improve the values of THD the multiphase topology of PFC is applied.…”
Section: The Charger Designmentioning
confidence: 99%
“…From the comprehensive study of different PFC topologies and their performance evaluations [1] it is found that, single switch converter topologies with current multiplier control in CCM operation leads to better stability. The push-pull and half-bridge (two-switch) converters have equal switching losses as compared to single switch converters such as flyback, Cuk SEPIC, and Zeta.…”
Section: Iiliterature Surveymentioning
confidence: 99%
“…Power factor pre-regulator topology, remains to be an ample choice for low power applications where the power transfer is unidirectional, because of its simplicity of design and control [3].…”
Section: Introductionmentioning
confidence: 99%